Observations on the growth of Penaeus monodon in a low saline culture pond - Guru, B C; Mohapatra, U C; Pal, S; Mohanty, A K (Indian Journal of Fisheries, 2011)
The shrimp Penaeus monodon grows toa good size with low saline water. A productionof 172.2 to 512.1 kg/ha crop has beenachieved (CMFRI 1988). Usually the salinelevel decreases in the tide water during monsoon.Attempts were made to study thegrowth of Penaeus monodon in a monoculturetide-fed pond of low saline water andto examine it9 viability, thereby exploringthe possibilities of culturing this species inthe potential areas where tide is the cheapwater source